The relevancy of learning community as a teaching-learning method in Christian education among the young professional Chinese Christians in the Philippines - Chua, Tessie Y. (Baguio City, Phils. Asia Baptist Graduate Theological Seminary, 2006)
Learning community method of education is one recent trend in teaching-learning style. This research seeks to determine the relevancy of learning community as a teaching-learning method in Christian education among the young professional Chinese Christians in the Philippines
In partial fulfillment of the requirements for the degree Doctor of Theology
A dissertation presented to the faculty of the Philippine Branch of the Asia Baptist Graduate Theological Seminary
Dissertation (D. Theo) - Asia Baptist Graduate Theological Seminary